Acute obstetric coagulopathy is associated with excess plasmin generation and proteolysis of fibrinogen and factor V - Peter W. Collins; Claire S. Whyte; Lucy de Lloyd; Anuj Narwal; Sarah F. Bell; Nicholas Gill; Rachel E. Collis; Peter V. Jenkins; Nicola J. Mutch (Blood Advances)
Abstract: Hemostatic impairment may exacerbate postpartum hemorrhage (PPH). Previously, we described a distinct coagulopathy, associated with multiple causes of PPH including placental abruption and amniotic fluid embolus, termed acute obstetric coagulopathy (AOC). AOC is characterized by very high plasmin/antiplasmin complexes and rapid depletion of functional fibrinogen and factor V (FV). To determine mechanisms underlying AOC, we investigated the plasma from 12 women with AOC (defined by raised plasmin/antiplasmin) and 21 with severe PPH (blood loss >2000 mL or placental abruption) without AOC. Plasma from patients with AOC had a fourfold increased ability to generate plasmin compared with those with severe PPH without AOC (P < .0002). AOC was associated with fibrinogen cleavage in the circulation, demonstrated by fragment D and other breakdown products (P < .0001). D-dimer was increased 36-fold in AOC compared with severe PPH without AOC, thrombin/antithrombin complexes were not raised. FV was reduced on western blot in AOC but not severe PPH without AOC (P < .001) suggesting FV cleavage. Confocal microscopy revealed similar clot structure between AOC and non-AOC samples, but both groups differed from nonbleeding pregnant controls. These data suggest that in AOC an excess of plasmin cleaves fibrinogen and FV in the circulation causing a specific, pathognomonic depletion of coagulation factors. Fibrin(ogen) breakdown products have cofactor function for tissue plasminogen activator, and these data are consistent with these breakdown products, enhancing plasmin generation and potentially driving aberrant plasmin generation in AOC. These results have implications for the clinical management of coagulopathy during PPH.